PENGARUH KUALITAS PRODUK, SOCIAL MEDIA MARKETING, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO : STUDI KASUS PENGGUNA SMARTPHONE OPPO DI KABUPATEN PATI - Wijaya, Rafly; Sijabat, Rauly; Meiriyanti, Rita (Gapenas Publisher, 2025)
This study aims to determine the effect of product quality, social media marketing, and brand image on purchasing decisions for Oppo smartphone users in Pati district. The population in this study were Oppo smartphone users in Pati Regency, while the sample taken amounted to 100 respondents. This study uses non-probability sampling techniques, namely purposive sampling, where the sample is applied with certain considerations in accordance with the desired criteria. Data collection was carried out by distributing questionnaires via Google Form. The results showed that the product quality and brand image variables had a positive and significant effect on purchasing decisions, while the social media marketing variable had no significant effect on purchasing decisions